Stability study of oxaliplatin and doxorubicin for intraperitoneal administration with hyperthermia - V. Escudero-Ortiz; M.ª J. Duart-Duart; C. Pérez-Ruixo; J. J. Pérez-Ruixo; B. Valenzuela (Farmacia Hospitalaria)
Objective: To evaluate the in vitro physicochemical stability of oxaliplatin anddoxorubicin when the in vivo hyperthermic intraperitoneal conditions arereproduced. Methods: Three solutions were prepared, A (oxaliplatin 200 mg/L), B(doxorubicin 15 mg/L) and C (oxaliplatin 200 mg/L with doxorubicin 15mg/L) in glucose 5%. The three solutions were subjected to the maximumtemperature reached in vivo (49° C) for two hours. Physical stability wasfocused on visual control of particles or precipitates in solutions, dischargeof gases, odor and color. Samples were taken every 15 minutes and thechemical stability was evaluated by determining the concentration of oxaliplatinand doxorubicin remaining in the samples. Oxaliplatin concentrationswere determined by atomic absorption graphite chamber whiledoxorubicin was determined by high performance liquid chromatography.The chemical stability criteria selected was the one described by the AmericanPharmacopoeia, which sets a permissible variation range betweenthe 90-110% of the initial concentration. Results: During the assay there was no appearance of particles, precipitatesin the samples, discharge of gases, nor colour changes in the solutions. Thesamples showed a remaining concentration of oxaliplatin and doxorubicinwithin the 90-110% limit. The stability of the samples that follow to twocycles of freeze-thaw after hyperthermia was also found within the specifiedlimits. Conclusion: A, B and c solutions in 5% glucose, are physically and chemicallystable at 49° C for two hours. Under these conditions, these solutionscould be used with guarantees of stability in patients with peritoneal carcinomatosissubsidiary of intraperitoneal hyperthermic chemotherapybased in these antineoplastic agents.